An Assessment of The Outstanding Universal Value of The Mardin Cultural Landscape Area and The UNESCO World Heritage List Nomination Process - Geyik, Nazli Ece; Turgut, Sirma (KARE PUBL, 2023)
Human beings have felt the desire to preserve their own produc-tion throughout history. In the process, protection approaches have changed, and over time, they have evolved from single struc-ture scale to structure groups and the settling scale. In this con-text, the phenomenon of protection has expanded by taking the tangible and untangible values produced in living areas into its own context. To this end, cultural and natural values, which are inherited from the past and are wanted to move to the future, are protected by universal qualifications and the common legacy of humanity. UNESCO gives the status of World Heritage(WH) to natural formations, monuments and sites that are internation-ally important and therefore worthy of admiration and protec-tion. The values are protected in a universal dimension with the Convention on the Protection of World Cultural and Natural Heritage, which was implemented by UNESCO on December 17, 1975. In 1983, Turkey adopted the relevant agreement as the entity state. Thus, the natural and cultural values in Turkey have started to enter the universal-sized world heritage list. Mardin has been on the temporary list since 2000 and has been nomi-nated for World Heritage List. It has been home to many civiliza-tions since the 2000 B.C. and is now an ancient city with mul-ticolor and multi-layered socio-cultural and physical structures. The city,which is characterized by its historical structures and texture and socio-cultural components as world heritage, is an important example of cultural landscape with its tangible and un tangible cultural values. The method of study was determined by evaluating literature by examining primary and secondary sources with on-site observations. In this study, the nomination process for. Mardin's World Heritage List (WHL) is intended to reveal the historical memory and structures of the city, its cultural identity and its outstanding Universal values(OUV). In this context, all the interventions made for the city were evaluated and recommen- dations were made to transfer Mardin's tangible and untangible values as a whole to future generations and to be included in the World Heritage List as the concept of cultural landscape.-
Keywords: World heritage site; Mardin cultural landscape area; Mardin urban conservation site; cultural landscape; outstanding universal value; Public Administration